CRISIS OF PROPERTY CREDIT ACCESS IN ACEH: THE ROLE AND CHALLENGES OF BPRS IN SUPPORTING THE HOUSING SECTOR - Siti Nurfajri (GREET, 2025)
This study examines the crisis of property credit access in Aceh with a specific focus on the role of Bank Perkreditan Rakyat Syariah (BPRS) in supporting the housing sector. Using a mixed-methods approach that integrates quantitative data with qualitative stakeholder perspectives, the research identifies systemic barriers such as limited financial literacy, regulatory restrictions, and insufficient capital, which constrain access to housing finance. Findings indicate that only about 30% of the Acehnese population has access to formal financial services, while the province faces a housing backlog of approximately 150,000 units. BPRS has contributed significantly by financing over 20,000 housing units through Sharia-compliant mechanisms, especially benefitting rural low-income households. However, challenges remain, including competition from conventional banks, rising construction costs, and limited digital infrastructure. Comparative insights from other regions, such as West Java and Malaysia, suggest that integrating fintech and cooperative financing models can enhance operational efficiency and outreach. The novelty of this study lies in its dual emphasis on the socio-cultural embeddedness of Islamic finance in Aceh and the structural reforms required to expand financial inclusion. Policy recommendations highlight the need for regulatory reform, technological adoption, and strengthened community partnerships to transform the housing sector. This research contributes to both academic discourse and practical policymaking by offering strategies for sustainable housing finance in post-disaster and post-conflict contexts.